P-156: Alignment of Ferroelectric Liquid Crystals with the Substrates Processed by Plasma-Beam - Hegde, Gurumurthy; Murauski, Anatoli; Chigrinov, V. G.; Kwok, Hoi Sing (Blackwell Publishing Ltd, 2008)
Plasma beam procedure earlier adapted for alignment of nematic liquid crystals and reactive mesogens is successfully applied for alignment of ferroelectric liquid crystals. Highly uniform alignment of “chevron” structure (before electrical treatment) and “quazi bookshelf” structure (after electrical treatment) are realized. In the latter case, the contrast of bistable switching is larger than 350:1 for 650 nm wavelength. This makes the non-contact plasma alignment procedure especially attractive for high contrast bistable LCD on LCOS base particularly used in PDA and E-books. Fast switching and realization of gray scale in the plasma beam aligned FLC cells makes this technique also promising for full color displays including color TV LCD.